Preclinical development of PR006, a gene therapy for the treatment of frontotemporal dementia with progranulin mutations: Molecular and cell biology/endosomal‐lysosomal dysfunction. (7th December 2020) - Heckman, Laura D.; Burstein, Suzanne R.; Brandes, Alissa; Wong, Li Chin; Yang, Zhaohui; Lin, Hsuan‐Ni; Fenn, Tim; Nelson, Stuart; Aziz, Zarah; Kamalakaran, Sid; Garimalla, Swetha; Haller, Jorge; et al.
Abstract: Background: Frontotemporal dementia (FTD) caused by GRN haploinsufficiency (FTD‐GRN) represents 5‐10% of all FTD cases. GRN encodes progranulin, a glycoprotein that is essential for normal lysosomal function and neuronal survival. FTD‐GRN patients exhibit approximately 50‐70% reduction in progranulin levels. We are developing PR006, an AAV vector designed to deliver the GRN gene, for FTD‐GRN patients with a goal of slowing or stopping disease progression. We aimed to evaluate the efficacy of PR006 in preclinical models of FTD‐GRN. Method: We evaluated the efficacy of PR006 in vitro using neurons differentiated from human induced pluripotent stem cells (iPSCs). iPSC‐derived neurons from individuals carrying GRN mutations exhibit reduced progranulin levels and decreased activation of the lysosomal enzyme cathepsin D. Additionally, we assessed the therapeutic effects of PR006 in vivo using a Grn knockout (KO) mouse model of FTD‐GRN. Grn KO mice exhibit progressive brain‐wide lipofuscinosis, ubiquitin accumulation, microgliosis, and neuroinflammation. PR006 was administered by intracerebroventricular (ICV) injection to Grn KO mice, and vector biodistribution, progranulin levels, lysosomal alterations, and neuroinflammation were assessed. Nonhuman primates (NHPs) were used to assess the safety and tolerability of PR006. Result: PR006 transduction in iPSC‐derived FTD‐GRN mutation carrier neurons resulted in robust, dose‐dependent secretion of progranulin and restored cathepsin D maturation. In the Grn KO mouse model, ICV PR006 treatment was well‐tolerated and resulted in broad vector biodistribution and increased progranulin expression in biofluids and tissues. PR006 treatment in the Grn KO mouse model decreased lipofuscinosis, ubiquitin accumulation, and expression of neuroinflammatory markers in the brains of these animals. PR006 treatment in NHPs was well‐tolerated and resulted in broad vector biodistribution and progranulin expression in the central nervous system and the periphery. Conclusion: These in vitro and in vivo preclinical studies demonstrated that PR006 effectively increased expression of progranulin and reduced pathological features of FTD‐GRN, supporting clinical development of PR006 for patients with this disease.